(untitled) (American International Journal of Business and Management Studies, 2020)
This research work focused on the effect of alternative dispute resolution dimensions on employees’ performance in Nigeria work organizations using a theoretical perspective. The information was sourced from text books, journal articles and internet materials. The study revealed that alternative dispute resolution dimensions or mechanisms such as mediation, arbitration, facilitation, conciliation, negotiation, collaboration, compromise, mini-trial, expert determination, good governance and communication has a positive and significant effect on employees’ performance in Nigeria work organizations. It also found that alternative dispute resolution has a significant influence on employees ‘performance in the workplace. And there is also a substantial correlation between alternative dispute resolution and employees’ performance in Nigeria work organizations. The study recommended that management as well as administrators should adopt ADR mechanisms/dimensions in resolving disputes or conflicts among parties in Nigeria work organizations in order to reduce cost, save time or avoid delay and being fast in reaching a consensus agreement as well as compromise.